APPROPRIATE IN THE SHARIA ECONOM APPROPRIATE IN THE SHARIA ECONOMY: DIGITALIZATION FOR 3 KG LPG SUBSIDY - Rofik, Akhmad; Vidiati, Cory; Faiz Amin, Nur M. (Program Studi Ekonomi Syariah Universitas Muhammadiyah Bandung, 2025)
Implementation of manual recording in the distribution of 3 Kg LPG often faces problems of inaccuracy of targets and inefficiency. One of them is due to misuse by retailers, they take advantage of loopholes in the manual system to buy subsidized LPG from the base and resell it above the Highest Retail Price (HET) to the public, including those who should not be entitled. This practice causes price distortion and makes subsidies not fully enjoyed by the target audience. The 3-kg LPG subsidy program in Indonesia aims to provide affordable energy access for communities in need. This study seeks to explore the role of digitalization—specifically through the implementation of the Merchant Apps—in realizing the principle of wadh'u asy-syai’ fi mahallihi (placing something in its proper context) within the framework of Islamic economics in the distribution of subsidized 3-kg LPG. This study uses a qualitative method with a case study at PT. Sinar Aurora Abadi. The analysis reveals that the Merchant Apps significantly enhance targeting accuracy through NIK (National Identification Number) verification and purchase limitations, while also improving distribution efficiency via digitized recording and reporting systems. These findings align with key principles of Islamic economics, including justice (‘adl), public benefit (maslahah), moderation and efficiency (iqtishad), and trustworthiness (amanah). Nonetheless, the implementation of the Merchant Apps also faces several challenges, particularly in relation to digital infrastructure, digital literacy, and system reliability. This study concludes that digitalization through the Merchant Apps holds strong potential for optimizing the distribution of the 3-kg LPG subsidy, making it more targeted, efficient, and accountable in accordance with Islamic economic values. Continuous efforts to address these challenges and to develop the application inclusively are essential to achieving these goals.